2022
DOI: 10.47067/ramss.v5i1.203
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Relationship between Character Strength and Religiosity of University and Madrassa Students

Abstract: This study explores the religiosity and character strength amongst university and madrassa students in Punjab, Pakistan. Additionally, the study determined the relationship between character strength and religiosity of madrassa and university students. The convergent mixed-method research design was applied for the study. The survey sample consists of 896 respondents selected through a multi-stage sampling technique. This sample includes 640 students (320 from universities and 320 from madrassas) and 256 teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
0
0
1
Order By: Relevance
“…Character strength adalah sifat kepribadian positif yang penting bagi identitas seseorang, berkontribusi untuk kebaikan yang lebih besar, dan menghasilkan kesejahteraan yang positif dan kesehatan untuk diri sendiri dan orang lain [15]. Character strength terdiri dari enam aspek yang dibangun oleh 24 character strength, yaitu kearifan dan pengetahuan (wisdom and knowledge), keteguhan hati (courage), perikemanusiaan dan cinta kasih (humanity and love), keadilan (justice), kesederhanaan (temperance), dan transendensi (transcendence) [16].…”
Section: Pendahuluanunclassified
“…Character strength adalah sifat kepribadian positif yang penting bagi identitas seseorang, berkontribusi untuk kebaikan yang lebih besar, dan menghasilkan kesejahteraan yang positif dan kesehatan untuk diri sendiri dan orang lain [15]. Character strength terdiri dari enam aspek yang dibangun oleh 24 character strength, yaitu kearifan dan pengetahuan (wisdom and knowledge), keteguhan hati (courage), perikemanusiaan dan cinta kasih (humanity and love), keadilan (justice), kesederhanaan (temperance), dan transendensi (transcendence) [16].…”
Section: Pendahuluanunclassified
“…According to Niemic (2020), using their strengths will help individuals find more purpose in life. Engaging in bodily worship of Allah, recommended acts, and sinful Religious commitment reflects individual religiosity, where religiosity supports individuals to commit to religion (Ashfaq, 2022). The results of research conducted by Ashfaq (2022) show that religiosity plays a significant role in promoting student character strength, which means that increased religiosity leads to higher student character strength.…”
Section: Tazkiya (Journal Ofmentioning
confidence: 99%
“…Students' contextual and adaptive growth benefited from the features' emphasis on a factual understanding of the universal components of character strengths. Furthermore, Ashfaq (2022) found that students' levels of religiosity and character strengths were positively correlated, and they advocated for a comprehensive and succinct study of students at both public and private universities and Islamic schools. Last but not least, Stuntz (2019) demonstrated that while there was considerable variation in the contextualization level of comprehension, the majority of the variance was moderate.…”
Section: Introductionmentioning
confidence: 99%